ANALISIS SISTEM BAGI HASIL ANTARA SHAHIBUL MAAL DAN MUDHARIB PADA PETANI PENGGARAPAN PADI DI DESA SENAUNG KEC JALUKO KAB MUARO JAMBI - Ahmad Dany Kuslima; Efni Anita; Rohana Rohana (Jurnal Kajian dan Penalaran Ilmu Manajemen, 2023)
The purpose of this study was to find out the profit sharing system carried out by rice field owners with rice cultivators in Senaung Village, Jaluko District, Muaro Jambi Regency and to find out the rights and obligations carried out by Shahibul Maal and Mudharib to rice cultivating farmers in Senaung Village, Jaluko District, Muaro Jambi Regency. As well as to find out the constraints faced by Shahibul Maal and Mudharib on rice cultivating farmers in Senaung Village, Jaluko District, Muaro Jambi Regency. The analytical approach used in this research is qualitative-descriptive. The results showed that the profit-sharing system that occurred in Senaung Village between Shahibul Maal and Mudharib was based on an agreement between the two parties according to local customary law that applies for generations, where custom is used as a source of law that can be obeyed by the local community and Profit sharing agreements that occur are generally carried out verbally with mutual trust among members of the community. Farmers' obligations that must be carried out to support production results are starting from the management preparation stage, the rice seed preparation stage, the next stage is starting to transfer the seedlings, the planting season preparation stage, rice planting, after the rice plants are 15, 25 and 45 days old, fertilization is carried out. After fertilization is carried out grazing between the rice fields, when the rice is 60 days old, pest control is carried out, the final stage is harvesting.